PENINGKATAN PRODUKTIVITAS TANAH DAN TANAMAN OLEH PUPUK ORGANIK DIPERKAYA BAKTERI PELARUT FOSFAT ASAL LEBAK - Neni Marlina; Rausthu Galang Bamullo; Rika Septiani; Rosmiah; Gusmiatun; Maria Lusia; Ika Paridawati; Dessy Tri Astuti; Berliana Palmasari; Fitri Yetty Zairani; Joni Phillep Rompas; Burlian Hasani (Altifani Journal: International Journal of Community Engagement, 2024)
The village of Talang Balai Baru 1, located in the sub-district of Tanjung Raja in the Ogan Ilir Regency, is characterized by a type of land known as lowland, locally called “lebak” land, which is characterized by low soil fertility. This factor, among others, contributes to a decrease in crop productivity. To address this challenge, it is imperative to employ organic fertilizer in optimal amounts. Specifically, the harvested straw is primarily incinerated, with a limited portion being utilized as chicken manure fertilizer. Despite the abundance of local resources like chicken manure and straw, they are underutilized. Therefore, there is a need to harness these resources for the production of organic fertilizers enriched with phosphate-solubilizing bacteria (PSB). This enriched organic fertilizer is expected to provide essential nutrients to plants and improve soil fertility, thereby boosting soil and crop productivity. The project, conducted from July 29, 2024, to August 27, 2024. The method employed in this study is counseling and socialization regarding the production of BPF-enriched organic fertilizer and its subsequent application by partner farmers. The results of this counseling and socialization demonstrate the high level of support among the residents of Talang Balai Baru 1 Village for this program, as evidenced by their ability to utilize BPF-enriched organic fertilizer on their respective fields. This will contribute to an enhancement in soil and plant productivity.